THE IMPACT OF INTERPERSONAL COMMUNICATION ON EMPLOYEE PERFORMANCE DURING WORK FROM HOME - Nurul Rezky Amalia; Andi Anto Patak; Lely Novia (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2023)
Interpersonal communication is the process of sharing information, ideas, feelings, and opinions from two or more people, verbally and non-verbally. This study aimed to determine the effect of interpersonal communication on employee performance during work from home. This data analysis uses descriptive qualitative. The subjects in this study were PDAM Makassar employees, with six people selected using purposive sampling. The results of this study indicate that there is an influence of interpersonal communication on employee performance during work from home. This is because their communication is effective, so their performance is also good. The better the interpersonal the interpersonal communication among employees, the better the performance result.